Bilateral Variation of Internal Iliac Artery - Yousef Mohamadi; Heydar Toolee; Gholamreza Hassanzadeh (Negah Institute for Scientific Communication, 2017)
Understanding anatomical variations can help physicians achieve better results in clinical practice. During routine dissection, we found variations in the branches of Internal Iliac Artery (IIA) of a 65-year-old Iranian female cadaver. The IIA ended by dividing to an unusual smaller anterior and a greater posterior trunk which was branched to the inferior gluteal arteries. Both pelvis and the uterine artery were separated from the umbilical artery in the left side. In addition, the left iliolumbar artery arose from the main trunk of IIA. Although this cadaver had some uncommon variations, the findings are significant from clinical perspective.